Radiographic Findings of Bisphosphonate-Related Osteonecrosis of the Jaws: Comparison with Cone-Beam Computed Tomography and Panoramic Radiography - NAMDAR PEKİNER, FİLİZ MEDİHA (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2017)
Objective: The aim of this study is to assess radiographic findings of bisphosphonate-related osteonecrosis of the jaws (BRONJ) and to evaluate the efficiency of cone-beam computed tomography (CBCT) and panoramic radiography (PR) by comparing with each other. Materials and Methods: The data of 46 patients treated with bisphosphonates for at least 1 to 10 years were retrospectively examined. 27 patients were selected for study group. The first inclusion criteria was an available CBCT or PR. The patients had at least one clinical symptom of exposed bone, intraoral or extraoral swelling and purulent secretion or fistula formation. In accordance with the position papers of the American Association of Oral and Maxillofacial Surgeons, the patients were classified into stages. CBCT and PR images were evaluated by dividing the jaws in 6 segments. Presence of bone sclerosis, cortex irregularity, persistent sockets, periosteal response, sequestration, and osteolysis were recorded. Results: The radiographic findings of BRONJ were mostly determined at posterior mandible with Stage 2 predominancy. Fifteen patients (55.6%) had previous tooth extraction. 9 of them had exposed bone at the same time. Seven patients had exposed bone without extraction. CBCT findings (P < 0.01) except persistent socket (P = 0.157) were found statistically significant by comparison with PR. Extraction socket finding was detected the same in segments with a percentage of 90.9%. Conclusion: This study showed that CBCT findings except extraction socket were significantly higher than PR. CBCT combined with clinical examination can be used effectively to determine the borders of effected areas especially at advanced cases.
Keywords: Bisphosphonate-related osteonecrosis of the jaws; cone-beam computed tomography; panoramic radiography